Synthesis of some Heterocyclic Compounds from 1,4-Benzoxazine-3-one - Omar A. Salih (College of Education for Pure Sciences, 2013)
Abstract The compound (1) was synthesized by reacting 2-amino phenol with ethyl bromo acetate.The treatment of ethyl bromo acetate with compound (1) gave (2), While compound (3) was produced by reacting hydrazine hydrate with compound (2). Compound (3) was used as precursor to prepare (4-12) by reacting it with different chemical reagents. The reaction of (11) with thioglycolic acid, 3-chloro perbenzoic acid afforded (13,14) respectively, while compound (15) was prepared from the reaction of (12) with chloro acetyl chloride. The products were identified by physical, chemical and spectroscopic methods.